Sintesis Hidrogel Pektin – Gelatin dengan Penambahan Ekstrak Kulit Buah Naga Sebagai Kandidat Pembalut Luka Bakar - Fadhil Muhammad Tarmidzi; Inggit Kresna Maharsih; Tina Raihatul Jannah; Cici Sari Wahyuni (Politeknik Negeri Malang, 2020)
Wound dressing technique currently applies modern wound care methods by maintaining the environmental isolation of the wound in a closed and moist state. There are several types of wound dressing that have been developed, one of them is hydrogel. Hydrogel is sheet-shaped wound dressings which have the ability to absorb exudate and have good stability acidic pH that can be used for the treatment of burns. In this study, hydrogel were made using natural polymers such as pectin and gelatin. The two polymers were combined using crosslinking method with the addition of citric acid as a crosslinking agent. The addition of citric acid has affect on the characteristics of the hydrogel material produced, therefore the right amount is needed to obtain a hydrogel with good mechanical properties. Hydrogel also added by an active substance in the form of flavonoids from dragon fruit peel extract that can be used as a wound dressing to cure burns. This study resulting hydrogel with a concentration of 4% citric acid (Hydrogel CA 4%) produced highest value of swelling, tensile strength, and elongation are 890%, 0.05 Mpa, and 200%, repectively. The mechanical properties of Hydrogel CA 4% was proved by FTIR test that had been carried out, namely the presence of C=O carbonyl group as a result of the esterification reaction that occurred between the polymers and citric acid in the absorption area of 1733.9 cm-1.